Phage Mu enlists the β-sliding clamp for late gene transcription - Khang Ho; Rasika M. Harshey (Proceedings of the National Academy of Sciences, 2026)
The phage Mu C protein (MuC), along with core RNA polymerase (RNAP) and σ 70 , is required for transcription of phage late genes. We found that overexpression of MuC was lethal in Escherichia coli and observed that host replication was overinitiating under these conditions. Suppressors of MuC lethality mapped to dnaA , diaA , and dnaX . DnaA initiates replication at oriC , assisted by DiaA. Reinitiation is prevented by hydrolysis of ATP-DnaA to ADP-DnaA by Hda and DnaN (β-sliding clamp or Clamp). DnaX, the tau/gamma subunit of Pol III, is part of the Clamp loader complex. Coexpression of hda and dnaN rescued MuC lethality. This result suggested that MuC was interfering with either Hda or DnaN. We noticed that MuC contains two near-consensus Clamp-binding motifs (CBM), one at the N terminus and one at the C-terminus. Changing the consensus residues of either CBM abolished MuC lethality, abrogated MuC-dependent transcription, and reduced plaque-forming units. Inactivation of a ts Clamp through temperature shift specifically inhibited MuC-dependent transcription but not σ 70 -dependent transcription. We show that MuC interacts with the Clamp to activate late gene transcription both in vivo and in vitro. This study demonstrates the involvement of the E. coli Clamp, a processivity factor essential for DNA replication, for transcription by E. coli RNAP. We observed that members of the Mor/MuC family of transcription factors all possess at least one CBM, suggesting that engaging the Clamp for transcription is likely to be more prevalent than hitherto recognized.